2019
DOI: 10.5500/wjt.v9.i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors and adverse effects in kidney transplant recipients: A meta-analysis

Abstract: BACKGROUND The adverse renal effects of proton pump inhibitors (PPIs) are increasingly recognized in both the general population and patients with chronic kidney disease. Several pharmacokinetic studies have also raised concerns regarding the interaction between PPIs and immunosuppressive drugs in transplant patients. Whether the adverse effects of PPIs have a clinical significance in kidney transplant recipients remains unclear. We performed this meta-analysis to assess the risk of adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
(69 reference statements)
0
19
1
Order By: Relevance
“…In a recently published meta-analysis, a similar risk of hypomagnesaemia among KTR was demonstrated (pooled OR = 1.56, 95% CI 1.19-2.05) [30]. This meta-analysis by Boonpheng et al was based on one published paper and seven abstracts presented at medical conferences.…”
Section: Discussionmentioning
confidence: 94%
“…In a recently published meta-analysis, a similar risk of hypomagnesaemia among KTR was demonstrated (pooled OR = 1.56, 95% CI 1.19-2.05) [30]. This meta-analysis by Boonpheng et al was based on one published paper and seven abstracts presented at medical conferences.…”
Section: Discussionmentioning
confidence: 94%
“…9,33 With significantly higher rates of magnesium supplementation in the PPI arm, this study added to the body of evidence that PPI use significantly increases hypomagnesemia in the transplant population. 15,[18][19][20]25 The average time of receipt of PPI or H2RA was several years, despite the majority of patients having no documented GI issues or other compelling reason for therapy posttransplant. At this center, there is a pharmacist present in the outpatient clinic setting but due to high patient volumes not every patient is assessed at every visit by a pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Previous studies of PPI use in the kidney transplant population have mainly evaluated the shortterm risk of rejection given that PPIs reduce gastric acidity and may alter absorption and serum levels of MPA. [12][13][14][15] Studies have demonstrated that the formulation of MPA may determine the effect of PPI co-administration, with mycophenolate mofetil (MMF) exhibiting significantly decreased area under the curve that has not been consistently seen with enteric-coated mycophenolate sodium (EC-MPS), although reductions in the active metabolite mycophenolic acid glucuronide have not been shown to consistently be impacted by PPI therapy with either formulation. 16,17 Other transplant studies have demonstrated associations between PPI use and hypomagnesemia, Clostridium difficile infections, iron deficiency anemia, and increased fracture risk.…”
mentioning
confidence: 99%
See 2 more Smart Citations